Ontogenetic dietary shifts and bioaccumulation of diphenhydramine in Mugil cephalus from an urban estuary. (June 2017) - Haddad, Samuel P.; Du, Bowen; Scott, W. Casan; Saari, Gavin N.; Breed, Christopher; Kelly, Martin; Broach, Linda; Chambliss, C. Kevin; Brooks, Bryan W.
Abstract: Though bioaccumulation of pharmaceuticals has received attention in inland waters, studies of pharmaceutical bioaccumulation in estuarine and marine systems are limited. Further, an understanding of pharmaceutical bioaccumulation across size classes of organisms displaying ontogenetic feeding shifts is lacking. We selected the striped mullet, Mugil cephalus, a euryhaline and eurythermal species that experiences dietary shifts with age, to identify whether a model base, diphenhydramine, accumulated in a tidally influenced urban bayou. We further determined whether diphenhydramine accumulation differed among size classes of striped mullet over a two year study period. Stable isotope analysis identified that ontogenetic feeding shifts of M. cephalus occurred from juveniles to adults. However, bioaccumulation of diphenhydramine did not significantly increase across age classes of M. cephalus but corresponded to surface water levels of the pharmaceutical, which suggests inhalational uptake to diphenhydramine was more important for bioaccumulation than dietary exposure in this urban estuary. Highlights: Studies of pharmaceutical bioaccumulation in estuarine and marine systems are limited. Medicine accumulation dynamics associated with ontogenetic feeding shifts is lacking. Diphenhydramine did not differ across mullet age classes demonstrating feeding shifts. Mullet bioaccumulation of diphenhydramine appears driven by inhalational exposure.